Spatio-temporal patterns and interactions with honeydew-producing Hemiptera of ants in a Mediterranean citrus orchard - Pekas, Apostolos; Tena, Alejandro; Aguilar, Amparo; García-Marí, Ferran (2017)
The role of ants in the citrus agro-ecosystem is controversial and understanding their ecology may help to clarify their function. The present study determined the daily and seasonal foraging patterns, the spatial distribution, the feeding sources and the associations with honeydew-producing Hemiptera of three ant species that forage in citrus canopies. The dominant ants Pheidole pallidula (Nylander) (Myrmicinae) and Lasius grandis Forel (Formicinae) foraged in mutually exclusive territories within the field, although they both shared their territory with the subordinate Plagiolepis schmitzii Forel (Formicinae), a distribution pattern known as 'ant mosaic'. The observed mean overlap for the spatial distribution was significantly lower than the generated by null models, providing strong evidence of spatial interspecific competition, especially between the two dominants. Ants ascended to the canopies from April until November. Colony nutritional requirements and temperature probably shape their seasonal foraging patterns. The daily activity pattern of P. schmitzii was strictly diurnal, whereas L. grandis and P. pallidula were active during the entire day. The ants' diet in the canopies consisted principally of hemipteran honeydew, whereas citrus nectar and predation/scavenging did not represent important food sources. More than 60% of the total honeydew sources and 100% of the citrus mealybug Planococcus citri colonies were tended by ants during spring and summer.